Can sustainable practices protect investors during financial market instability? a multi-sector analysis during the COVID-19 pandemic - Nirino, Niccolo; Petruzzella, Felice; Alam, Gazi Mahabubul; Campobasso, Francesco (Emerald Publishing, 2022)
Purpose: The aim of this study is to analyse the relationship between firms' sustainable practices and corporate financial performance during the COVID-19 pandemic. Specifically, this study aims to analyse the effect of sustainable practices on firms' stock returns during and after the first COVID-19 pandemic emergency. Design/methodology/approach: A quantitative study was conducted to determine the impact of sustainable practices on firms' stock returns, using a sample of 1,418 European listed firms. In particular, we tested the effect of environmental (E) and social (S) scores, providing a multi-sectoral analysis in order to consider sector specificities. Findings: The empirical outcomes indicate the existence of a negative (weak) or null relationship between sustainable practices and stock returns, failing to provide evidence that these practices are able to protect shareholders value during times of crisis. Practical implications: The results obtained made it possible to highlight significant implications for investors and practitioners. They may have particular attention in evaluating firm's sustainable practices trying to understand more precisely the value that such practices can have for the company and its shareholders. Originality/value: This article is part of the stream of studies that analysed the impact of sustainable practices on stock returns during a period of crisis in order to contribute to filling the gap due to the lack of consensus and the mixed results in the literature.